Technology and empirical dynamics of specialization in open economies - Michael Stolpe (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1994)
This paper applies Markov chain analysis to examine the empirical dynamics of sectoral specialization in open economies. At issue is here persistence and the hypothesis of hysteresis in national patterns of industrial specialization, often claimed as an implication of strong path dependence in the evolution of high-technologies specific to certain industries. The evidence from twelve OECD member countries' time series of value added in 17 manufacturing industries and from corresponding patent count data does not support the hypothesis of hysteresis based on nationally restricted knowledge spillovers from industrial research and development activities. On the contrary, there seems to be generally lower persistence in patterns of technological specialization than in the corresponding production specialization. Moreover, high persistence in some parts of manufacturing mostly disappears when taking into account changes in countries' relative factor endowments, which form the basis of dynamic comparative advantages. These findings cast doubt on the popular belief that a government can — by making cleverly designed and appropriately timed industrial policy interventions — secure a permanently larger share of certain industries for the national economy which are supposed to lock in first mover advantages in terms of particularly high rates of technological innovation and productivity growth.
Keywords: 330; Internationale Arbeitsteilung; Neue Wachstumstheorie; Technischer Fortschritt; Hysteresis; Theorie